2004
DOI: 10.1007/s10803-004-5294-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Parental Reporting of Regression in Children with Pervasive Developmental Disorders

Abstract: Information on age and nature of the onset of autism and other developmental disorders was obtained through review of parent completed developmental history; in addition information on the child's early development, diagnostic information, and information on parent characteristics was also obtained. In this relatively large series of cases the parents of children with autism were more likely than parents of children with other developmental disorders to report possible loss of developmental skills. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 15 publications
7
68
1
7
Order By: Relevance
“…Entretanto, foi percebida a necessidade de uma análise e uma comparação dos mesmos aspectos, obtidos a partir da perspectiva de indivíduos que enxergam esse mesmo alvo, mas com outro foco, como as terapeutas (11) . A consideração da perspectiva dos pais de crianças do espectro autístico quanto ao comportamento linguístico, cognitivo e social de seus filhos vem sendo colocada em um lugar de destaque, uma vez que estes passam a ser parceiros dos profissionais envolvidos no processo de intervenção, ajudando no monitoramento do nível de desenvolvimento destas crianças (12)(13)(14)(15) . Investigando o uso da informação do contexto familiar para direcionar a avaliação e o processo terapêutico, observouse que o uso dessas informações em processos de avaliação e terapia não geram problemas, podendo contribuir para a estabilidade e durabilidade da redução de comportamentos desafiantes alcançados por meio de uma abordagem funcional da comunicação (16)(17)(18) .…”
Section: Introductionunclassified
“…Entretanto, foi percebida a necessidade de uma análise e uma comparação dos mesmos aspectos, obtidos a partir da perspectiva de indivíduos que enxergam esse mesmo alvo, mas com outro foco, como as terapeutas (11) . A consideração da perspectiva dos pais de crianças do espectro autístico quanto ao comportamento linguístico, cognitivo e social de seus filhos vem sendo colocada em um lugar de destaque, uma vez que estes passam a ser parceiros dos profissionais envolvidos no processo de intervenção, ajudando no monitoramento do nível de desenvolvimento destas crianças (12)(13)(14)(15) . Investigando o uso da informação do contexto familiar para direcionar a avaliação e o processo terapêutico, observouse que o uso dessas informações em processos de avaliação e terapia não geram problemas, podendo contribuir para a estabilidade e durabilidade da redução de comportamentos desafiantes alcançados por meio de uma abordagem funcional da comunicação (16)(17)(18) .…”
Section: Introductionunclassified
“…Some parents report that their child displayed neither early signs of autism nor regression, a phenomenon that has been called developmental plateau 17,18 or stagnation. 19 Other studies have found evidence of both early signs of ASD and regression simultaneously present in the retrospective histories of children with ASD. 9,11,12,20 Questions about when and how behavioral signs of autism emerge may better be answered through prospective, rather than retrospective, studies.…”
mentioning
confidence: 96%
“…Approximetely 1/3 of the parents (%20-56) of autistic children report an early regression in their children (1,3,(77)(78)(79)(80)(81)(82). This regression takes place before 3 years of age, commonly between 18-24 months when the child was in the stage of 3-5 words vocabulary (73,78,83,84).…”
Section: Autistic Regressionmentioning
confidence: 99%
“…The children who regressed may be reported to be normal prior to the regression or have had some preexisting autistic features, which clearly to be worsened by regression (3,80). Almost half of the parents of children who experience AR report abnormalities in sociability, communication and/or cognitive development before the loss of skills (73,81,85,86). These findings underlie the controversy about the presence of an entirely normal phase before the regression.…”
Section: Autistic Regressionmentioning
confidence: 99%
See 1 more Smart Citation